Species and distribution of phytoflagellate cysts in surface sediment at Kungkraban bay, Chanthaburi province - Pasuram, Lamjiak; Paibulkichakul, Chalee; Lirdwitayaprasit, Thaithaworn; Srivilai, Dusit (Asia-Pacific Journal of Science and Technology, 2017)
Species composition and distribution of phytoflagellate cysts in the surface soil sediment were investigated at 13 stations around Kungkraban Bay. Nine stations were located inside the bay and the other four outside. Two cruises were operated in this study. The first cruise was conducted during 17-19 July, 2005 which represented the early rainy season samples. The second cruise was conducted during 9-12 November, 2005 which represented the late rainy season samples. Twelve types of cysts were found and all were Dinoflagellate cysts of which belong to the orders of Gonyaulacales, Peridiniales and Gymnodiniales and one unclssified cyst type. The dominant species were cyst of Protoperidinium sp.1 and the most common species were Protoperidinium sp.1, Protoperidinium sp.2, Lingulodinium polyedrum, Pheopolykrikos hartmannii, Spiniferites bulloideus and S. mirabilis. Dinoflagellate cysts were widely found in almost all stations. The abundance and diversity of dinoflagellate cysts during in late rainy season were higher than the early rainy season. This observation was clearly observed in the samples collected from the outside bay stations.